Radioactive Iodine-131 Therapy in the Management of Ectopic Thyroid Tissue - Omayma T. El-Shafie; Samir Hussain; Dilip Sankhla; Nicholas Woodhouse (Sultan Qaboos University Medical Journal, 2014)
The occurrence of ectopic lingual thyroid tissue was first reported over 100 years ago. We report an unusual presentation of ectopic thyroid tissue occurring in the submental area. A 27-year-old female presented to the Sultan Qaboos University Hospital in Muscat, Oman, in October 2011 with an 8 x 6 cm mass which caused difficulty in talking and a feeling of heaviness in the jaw. She was clinically and biochemically euthyroid upon presentation. The clinical diagnosis was confirmed by a technetium-99m thyroid scan, magnetic resonance imaging and fine needle aspiration. A single dose of 976 megabecquerels of radioactive iodine-131 resulted in hypothyroidism after three months and the complete disappearance of the swelling and associated symptoms. At a two-year follow-up, the patient was healthy and continuing lifelong replacement therapy with thyroxine.